PEMANFAATAN ABU SABUT KELAPA SAWIT DAN PENGARUHNYA TERHADAP KARAKTERISTIK BATAKO - Nur Aisyah Jalali (Universitas Negeri Yogyakarta, 2017)
ABSTRACT This study aims to determine the physical properties and quality of the concrete block that contain palm ash as a partial replacement of cement.The sample of concrete blocks measuring 40x20x10 cm with compositions 1 cement and 4 sand (volume ratio).Variations of the test specimen without palm ash and containing palm ash content with 5%, 10%, 15%, and 20% of the cement used.The test includes examining the size, the compressive strength testing, and water absorption.The test results showed that the length and width of the concrete blocks are still in the allowable limits, but the thickness does not meet standards. The results of compressive strength testing of concrete blocks with ash content 5%, 10%, and 15% are considered quality II, concrete blocks without ash and with ash content of 20% included in the quality III. The test results of water absorption for all variations of the mixture into the quality I and II Keywords: concrete block, palm fiber, measure, strength, water absorption ABSTRAK Penelitian ini bertujuan untuk mengetahui sifat-sifat fisis dan mutu batako akibat adanya abu sabut kelapa sawit (SKS) sebagai bahan pengganti sebagian semen. Benda uji berupa batako berukuran 40x20x10 cm dengan komposisi 1 semen dan 4 pasir (perbandingan volume). Variasi benda uji yakni batako tanpa abu SKS, dan batako dengan abu SKS sebesar 5%, 10%,15%, serta 20% dari kebutuhan semen. Pengujian meliputi pemeriksaan ukuran, pengujian kuat tekan, dan penyerapan air. Hasil pemeriksaan ukuran menunjukkan bahwa panjang dan lebar batako masih berada dalam batas yang diperkenankan, tetapi tidak demikian dengan tebal batako. Hasil pengujian kuat tekan batako dengan kadar abu 5%, 10%, dan 15% masuk dalam mutu II, sedangkan batako tanpa kadar abu dan batako dengan kadar abu 20% masuk dalam mutu III (Balitbang Kimpraswil, 2003b). Hasil pengujian penyerapan air untuk semua variasi campuran masuk dalam mutu I dan II (Balitbang Kimpraswil, 2003b). Kata kunci: batako, sabut kelapa sawit, ukuran, kuat tekan, penyerapan air.